INTEGRATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES (ICT) IN SECONDARY EDUCATION IN THE ARAB SECTOR: PARENTAL ATTITUDES AND THE CHALLENGES OF THE DIGITAL DIVIDE - Hana Horany (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The integration of Information and Communication Technology (ICT) in education is vital for enhancing learning, expanding resource access, and fostering digital skills. This study explores parental attitudes toward ICT implementation in Arab high schools in Israel, focusing on its impact on learning, teaching, and school management processes. The research identifies key barriers, including cultural perceptions, limited infrastructure, and insufficient digital skills, which hinder effective ICT adoption.Using qualitative research methods, data was collected from interviews with 22 parents of high school students across 11 schools in northern and southern Israel. Findings indicate a dual perspective among parents: while recognizing the potential of ICT to enrich educational experiences, they express concerns about over-reliance on technology, health risks from prolonged screen time, and the erosion of traditional teacherstudent interactions. A significant digital divide was also observed, disproportionately affecting underprivileged households. This study introduces a novel focus on high school 6 parental perspectives within the Arab sector, emphasizing the need for targeted interventions. Recommendations include parent training programs to improve digital literacy, enhanced infrastructure support, and culturally sensitive strategies to bridge the gap between digital and traditional learning. These efforts can foster a balanced and inclusive educational environment, leveraging ICT’s benefits while addressing its challenges.